New species of the gorgoniian genus Pacifigorgia (Coelenterata: Octocorallia: Gorgoniidae) from Pacific Panama - Breedy, Odalisca; Guzman, Hector M. (Zootaxa, 2004)
Four new shallow water species of the genus Pacifigorgia were found in recent surveys along the Pacific coast of Panama. One of the species was only found in dense patches at two shallow seamount-like localities inside the Coiba National Park, Gulf of Chiriqu . Two other species were patchily distributed at several localities in the Gulf of Chiriqu . A fourth species was widely distributed around the gulfs of Chiriqu and Panama encompassing a broad range of habitats and depths. The new species are described and illustrated in detail with scanning electron micrographs (SEM) of the sclerites, and colour photographs of the colony forms. The suspected occurrence of a particular Pacifigorgia species for this region is confirmed and two other new records are added to the species list. With the new four species, a total of 15 are established for Panama, making 31 species for the eastern Pacific to date.